2018
DOI: 10.1371/journal.pgen.1007644
|View full text |Cite
|
Sign up to set email alerts
|

Hunchback is counter-repressed to regulate even-skipped stripe 2 expression in Drosophila embryos

Abstract: Hunchback is a bifunctional transcription factor that can activate and repress gene expression in Drosophila development. We investigated the regulatory DNA sequence features that control Hunchback function by perturbing enhancers for one of its target genes, even-skipped (eve). While Hunchback directly represses the eve stripe 3+7 enhancer, we found that in the eve stripe 2+7 enhancer, Hunchback repression is prevented by nearby sequences—this phenomenon is called counter-repression. We also found evidence th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Additional work will be necessary to determine whether this correlation between rising Hunchback levels and increased stripe activity can be reconciled with the counter-repression hypothesis proposed in ref. 80. Finally, we note that the striking absence of a direct functional role for Bicoid in the regulation of either phenomenon suggests that, while Bicoid is almost certainly necessary for the expression of eve stripe 2 (16), it does not play a direct role in dictating the magnitude or duration of eve stripe 2 transcription.…”
Section: Discussionmentioning
confidence: 84%
“…Additional work will be necessary to determine whether this correlation between rising Hunchback levels and increased stripe activity can be reconciled with the counter-repression hypothesis proposed in ref. 80. Finally, we note that the striking absence of a direct functional role for Bicoid in the regulation of either phenomenon suggests that, while Bicoid is almost certainly necessary for the expression of eve stripe 2 (16), it does not play a direct role in dictating the magnitude or duration of eve stripe 2 transcription.…”
Section: Discussionmentioning
confidence: 84%
“…Rather, we suggest that Hb may be preventing activation by Cad, despite its presence. Hb and Cad play antagonistic roles at the enhancers of other genes, such as even skipped (Clyde et al, 2003;Small et al, 1992;Vincent et al, 2018). Therefore, co-occupancy of the gt_(-3) enhancer by Hb and Cad is not unprecedented, but the mechanism by which Hb prevents gt activation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, deletion of Runt's C-terminal 25 amino acids, including the VWRPY motif, prevents Runt from activating slp1; however amino acids other that the VWRPY motif appear to be involved as Gro appears to play no role in regulating the DESE enhancer. Here we provide evidence that Runt activates SxlPe by interfering with Groucho mediated repression suggesting that Runt's role at SxlPe is as a counter-repressor (PINTO et al 2015;VINCENT et al 2018). First, we showed that deletion of just the Gro-interacting WRPY sequence rendered a runt transgene that normally provides full XSE function, unable to activate SxlPe (Fig.…”
Section: )mentioning
confidence: 65%
“…We found that deletion of the WRPY sequence eliminated Runt's ability to activate SxlPe, but that Runt's transcriptional activation function was restored when the higher-affinity WRPW sequence was used. Since Runt's ability to activate SxlPe depends both on the presence of a functional corepressor-interacting motif, and an intact DNA binding domain, the simplest interpretation is that Runt activates SxlPe by acting as a "counter-repressor" of Gro function (PINTO et al 2015;VINCENT et al 2018). We also demonstrate that Runt is needed only after the onset of Sxl…”
Section: Introductionmentioning
confidence: 64%